Structural and optical properties of narrowband Sc/Si multilayer at 46.5 nm - Wu, Jiali; Qi, Runze; Zhang, Zhong; Wang, Zhanshan (Frontiers in Physics, 2022)
The Ne VII line is an intense solar line emitted from the solar transition region located at 46.5 nm with a temperature of approximately 0.5 MK. The observation of a Ne VII line is important to deepen the understanding of solar physics. For observing the Ne VII line at 46.5 nm, we have proposed a narrowband Sc/Si multilayer that could avoid the other solar emission lines going to the observatory instrument. In this paper, Sc/Si multilayers with a Sc thickness ratio of 0.35 (conventional design) and 0.65 (narrowband design) were deposited. The microstructures of both multilayers were measured by grazing incidence X-ray reflectometry, X-ray diffraction, and transmission electron microscopy. The results showed that the interdiffusion at the Si-on-Sc interface was more significant than that at the Sc-on-Si interface in both multilayers. Compared with the conventional multilayer, the narrowband multilayer had a thinner Si-on-Sc interface width. The measured reflectivity of the Sc/Si multilayers with a Sc thickness ratio of 0.65 was 37.9% at 45.5 nm with a near-normal incident angle of 4.60 degrees. The bandwidth was 3.68 nm, which is narrow enough to observe the Ne VII solar line.